Import Share under International Oligopoly with Differentiated Products: Japanese Imports in U.S. Manufacturing - Yamawaki, Hideki; Audretsch, David A. (The Review of Economics and Statistics, 1988)
Hideki Yamawaki, David A. Audretsch, Import Share under International Oligopoly with Differentiated Products: Japanese Imports in U.S. Manufacturing, The Review of Economics and Statistics, Vol. 70, No. 4 (Nov., 1988), pp. 569-579